Differentially expressed and alternately spliced genes as a novel tool for genotoxicity: a computerized study in ATT-myc transgenic mice for the recognition of genotoxic and non-genotoxic chemical - Alghamdi, Mansour A.; El Nashar, Eman M.; Elalfy, Mahmoud; Al-Zahrani, Norah S.; Alshehri, Mohammed A.; El-Nablaway, Mohammad; Al-Khater, Khulood M.; Aldahhan, Rashid A.; El-Hadidy, Eman G.; Sleem, Fathy; Aljazzar, Ahmed; Borlak, Jürgen; et al. (Frontiers in Genetics, 2025)
BackgroundTransgenic mice and gene expression in analyses were employed to evaluate hazardous chemicals.MethodsMice received weekly doses of NDEA (75 mg/kg) for six weeks and twice-weekly doses of BHT (300 mg/kg) for eight weeks. Gene expression and splicing alterations in the livers of six transgenic mice for each treatment of NDEA and BHT were examined using the MouseExon10ST array.ResultsSix hybridizations revealed 645 genes with significant expression changes, and 181 genes showed both expression and splicing alterations (p < 0.01). Furthermore, 2021 genes demonstrated significant exon–group interactions, indicating potential alternative splicing. Pathway analysis identified enriched groups in GOMolFn, GOProcess, GOCellLoc, and Pathway classes, with a higher representation of alternatively spliced and expressed genes (p < 0.01).DiscussionAmong the top expressed genes was TAT, which encodes the mitochondrial enzyme tyrosine aminotransferase, involved in tyrosine metabolism and recognized as a novel tumor suppressor gene linked to hepatocellular carcinoma (HCC). Additionally, HNF-4, a transcription factor, plays a crucial role in TAT expression.ConclusionsThis method can be used to identify genotoxic compounds in the att-myc model for short-term toxicity.